MELATIH KETERAMPILAN KOMUNIKASI DAN KEMANDIRIAN BELAJAR SISWA MA MELALUI MODEL PENGAJARAN TERBALIK (RECIPROCAL TEACHING) PADA TOPIK PERTUMBUHAN DAN PERKEMBANGAN TUMBUHAN - Agustiningsih, Neneng (Jurnal BIOEDUIN, 2019)
The appropriate biology learning process provides learning experiences to understand concepts and processes of science, involves students actively to foster communication and independence of learning skills. One learning method that can be applied is the reciprocal teaching method. Therefore, the purpose of the study is 1) to find out the communication skills of female students and 2) to find out the differences in the independence of learning biology through the reverse teaching model (Reciprocal Teaching). This research is a quasy experiment with the design of Posttest Only Control Group Design through questionnaires. The results of the study using the hotelling T2 test showed a difference in female communication skills through the Reciprocal Teaching approach, and the difference in the learning independence of biology subject through the Reciprocal Teaching approach.